A comparative study of the tax measures for persons with disabilities in South Africa with those of Canada and the Republic of Ireland - Currie, Natasha (Rhodes University, Faculty of Commerce, Department of Accounting, 2020)
Literature indicates that tax relief measures for persons with disabilities are important as they align with the principle of equity in the allocation of the tax burden. They are a government intervention that assists in decreasing the financial burden of medical care for persons with disabilities. The right of persons with disabilities to an adequate standard of living is contained in the landmark Convention on the Rights of Persons with Disabilities and Optional Protocol, a treaty of the United Nations, which South Africa ratified in 2007. The objective of the research was to provide a comparative study of tax relief measures for persons with disabilities in South Africa with those of Canada and the Republic of Ireland, with a view to identifying potential areas for improvement in South Africa. The requisite information was primarily collected through an extensive analysis of the tax legislation in the jurisdictions. The research found that tax relief measures for persons with disabilities and their families in South Africa are limited when compared with those of Canada and the Republic of Ireland. The comparative study identifies a number of potential tax relief measures for implementation in South Africa.
Keywords: People with disabilities -- Taxation -- South Africa; People with disabilities -- Taxation -- Law and legislation -- South Africa; People with disabilities -- Taxation -- Canada; People with disabilities -- Taxation -- Law and legislation -- Ireland; People with disabilities -- Taxation -- Ireland